Macrophage Rewiring by Nutrient Associated PI3K Dependent Pathways - Sharif, Omar; Brunner, Julia Stefanie; Vogel, Andrea; Schabbauer, Gernot (Frontiers in Immunology, 2019)
Class 1 Phosphoinositide-3-Kinases (PI3Ks) have been widely studied and mediate essential roles in cellular proliferation, chemotaxis, insulin sensitivity and immunity. Here, we provide a comprehensive overview of how macrophage expressed PI3Ks and their downstream pathways orchestrate responses to metabolic stimuli and nutrients, polarizing macrophages, shaping their cellular identity and function. Particular emphasis will be given to adipose tissue macrophages, crucial players of insulin resistance and chronic metabolically triggered inflammation during obesity. An understanding of PI3K dependent wiring of macrophage responses is important as this is involved in various diseases ranging from obesity, type 2 diabetes to chronic inflammatory disease.